PENAMBAHAN BUBUR LABU KUNING TERHADAP PREFERENSI SAUS TOMAT-LABU KUNING - Seveline Seveline (Agroindustrial Technology, University of Trunojoyo Madura, 2017)
Tomato ketchup is a product favored by the people of Indonesia. The use of pumpkin as fillersubstance in the production of tomato ketchup is performed as an alternative to conventionaltomato ketchup filler substance. This study aims to determine the right balance between thetomato puree and pumpkin puree to produce a tomato ketchup that can be accepted byconsumers, without addition of coloring agents and other food additives. The results showedthat the quantity of tomato puree and pumpkin puree in proportion of 85 and 15 produces thebest tomato ketchup and has the same characteristics as the standard and is preferred by thepanelists, with a viscosity of 40300 cps, the water content of 61.53% and pH of 3.87.